What comes naturally? Relaxed Naturalism's new philosophy of nature - Hutto, Daniel D.; Robertson, Ian (Naturalism and Its Challenges, 2024)
Demarcating the limits of the natural continues to be topic of great philosophical controversy. This chapter seeks to further clarify pivotal differences between Relaxed, Scientific, and Liberal Naturalism on this important matter. It seeks to show how and why Relaxed Naturalism starts and ends in a different place than these other forms of naturalism. It seeks to explicate why embracing Relaxed Naturalism allows one to take up a different stance on what is involved in the philosophical endeavour of providing a philosophy of nature and deciding what comes naturally.
CRIS-Team Scopus Importer:2024-11-22